2013
DOI: 10.4103/0970-9290.118004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dental treatments on salivary immunoglobulin A of children with and without dental caries: A comparative study

Abstract: Mere quantitation of salivary IgA levels might have no reflection on the functional antibodies involved in caries process, and successful dental treatment alone does not alter the salivary IgA levels, suggesting a multifaceted approach to combat the cariogenic challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
2
4
0
1
Order By: Relevance
“…The sIgA provides immunity by inhibition of microbial adhesion, toxins, and enzyme neutralization and by reducing hydrophobicity in synergism with lactoferrin and lysozymes [21]. Studies conducted on children suggest increased susceptibility to dental caries due to deficiency of sIgA and increased expression during caries suggesting a protective role; however, there is contradiction on correlation between dental caries and sIgAs [22][23][24]. In addition, matrix metalloproteinases (MMPs) and cathepsins are associated with dental caries progression and pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The sIgA provides immunity by inhibition of microbial adhesion, toxins, and enzyme neutralization and by reducing hydrophobicity in synergism with lactoferrin and lysozymes [21]. Studies conducted on children suggest increased susceptibility to dental caries due to deficiency of sIgA and increased expression during caries suggesting a protective role; however, there is contradiction on correlation between dental caries and sIgAs [22][23][24]. In addition, matrix metalloproteinases (MMPs) and cathepsins are associated with dental caries progression and pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Similar conclusions have been reached by other authors, who note higher levels of sIgA in children susceptible to dental caries. [7][8][9][10] Al Amoudi et al 11 observe a similar relationship in children and also in their mothers. Higher levels of secretory IgA in saliva can be associated with the immune response to large numbers of bacteria from the Streptococcus mutans group in carious cavities, which are sites of retention for food debris and bacteria.…”
Section: Discussionmentioning
confidence: 89%
“…Do podobnych wniosków doszli inni autorzy, którzy w swoich badaniach stwierdzili wyższy poziom S-IgA u dzieci podatnych na próchnicę. [7][8][9][10] Al Amoudi i wsp. 11 zaobserwowali podobną prawidłowość u dzieci oraz dodatkowo u ich matek.…”
Section: Dyskusjaunclassified
“…Twenty-four studies reported s-IgA as outcome ( 14 17 , 27 , 31 , 43 , 52 , 61 63 , 68 , 75 , 77 , 79 , 80 , 86 , 88 , 90 , 94 , 99 , 102 , 105 , 107 ) ( Supplementary Table S4 ). Enzyme-linked immunosorbent assay (ELISA) was the method used in most of the studies (41.6%).…”
Section: Resultsmentioning
confidence: 99%